Kinszia Erickson: capstone - Erickson, Kinszia, artist (Colorado State University. Libraries, 2014)
The artist's statement: I have always been fascinated by the reactions that can be elicited through art, and I strive to draw a reaction from my own viewers. Much of my previous work relied on morbid or repulsive materials in order to shock the viewer, such as ashes, blood, and spiders. Though this work elicited a strong response, it was intense but quickly faded. Currently, I am pursuing a new series of work, one that still compels my audience to react to these pieces, but in a way that lasts and challenges the way they think of these items. Instead of revulsion, I am looking to fill my viewers with a sense of curiosity, nostalgia, loss, and honesty. The items that I have chosen to use are family keepsakes. These images and objects inspire me to question their history. I need to know why these photographs were taken and what made these moments worth capturing. I need to know how people felt when they held these items in their hands. These are the questions and thoughts that compel me to keep exploring these personal artifacts. It is my goal to successfully communicate the power and mystery that surrounds these items. I am memorializing people and memories by permanently placing them in my work, with the hope that my audience will be as moved by them as I am.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.